Smart airbag vest with integrated light turn signaling and location tracking - Alecsandra Marjorie G. Cerda; Mark Joseph B. Enojas; Gil Jr. Abengaña; Mylene B. Laid; Mark Joshua T. Revedizo; Rimmel James Torrenueva (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Research on road safety is continuously developing with the applications of sensors and technologies. Another area that draws the attention of the developers for road safety are in the road accident response. As the number of riders and cyclists increase, so do the accidents particularly at night where visibility is limited. This study presents a method of integration of inflatable safety vests for riders with light emitting diode LED signaling strips embedded in its front and back, and sensors to send the location of the rider when an accident happens. The LED strips are controlled using a wireless remote switch to make the rider more visible other than that embedded in the motorcycle or bicycle. The airbag will activate once an accident occurs and or the rider is detached from the motorcycle. A force-sensitive resistor (FSR) is used as a triggering device attached to the vest when an accident happens where a global positioning system (GPS) module will send the location and a map to a specific mobile number for response. Three trials were conducted to test the functionality of the LED lights for signaling. The device functioned well, that both the left, right, and standby mode were activated. The functionality of the location tracker is also tested in three different locations. The FSR was triggered and it gave the exact location by sending the coordinates and a link to view it on google maps with an average transmit and receive time of 3 seconds. It is recommended that the prototype be developed using light-weight materials and batteries.